Effect of swift heavy ions on an EPDM elastomer in the presence of oxygen: LET effect on the radiation-induced chemical ageing. (January 2015) - Ngono-Ravache, Y.; Damaj, Z.; Dannoux-Papin, A.; Ferry, M.; Esnouf, S.; Cochin, F.; De Combarieu, G.; Balanzat, E.
Abstract: With the aim of understanding the radiation effects of alpha particles on polymers, this paper analyses the role of the heterogeneity of energy deposition, at the nanometric scale, on the radiation-induced oxidation of an ethylene-propylene-diene elastomer based on 1, 4 hexadiene (EPDMh). This polymer was irradiated with 20 Ne, at various Linear Energy Transfer (LET), in the presence of oxygen. Macromolecular defects such as carbonyls, alkenes and alkynes were monitored on-line, using Fourier Transform Infrared Spectroscopy (FTIR), and their evolution as a function of both LET and irradiation dose were studied. Carbonyl group consists of various chemical functions which absorption bands overlap one another in a limited spectral area. The different components were extracted by curve fitting, allowing monitoring the specific evolution of each of these chemical functions as a function of the irradiation conditions. Among carbonyl containing functions, the creation of ketone groups is the most important. LET influences the alkene radiation chemical yield at initial dose and, apart from trans -vinylene, it also influences the dose evolution of their concentration. Conversely, LET has no significant influence on the total carbonyl concentration.